Importancia de la radio como medio tradicional en sectores rurales Vinces 2020 - García Mendoza, Omar Enrique (2020)
This case study is based on the analysis of the importance of radio in the rural sector of the Vinces canton, since the rural area comprises approximately more than half of its population. A research with a mixed approach was proposed: qualitative-quantitative, documentary and descriptive, with the use of inductive-deductive methods, applying survey and interview techniques, the study sample is made up of 384 people to whom The survey was applied to them, with the result that the majority of respondents listen to the radio, of the local radios the most tuned radio is Radio Paris, followed by radio La Noticia, the majority tune in to these media in the morning, the respondents Most of them state that if they consider that there is manipulation in the news, the majority believe that there should be programs with cultural content, and the majority believe that spaces should be given to citizens so that you participate actively giving your opinion. As conclusions, once the case study has been carried out, it has been observed that the communities of the rural sectors of Vinces have the most credible mass communication medium on the radio because they have not been able to experiment with other technologies due to the poor coverage they have. That is why they consider radio very important to receive information in their places of residence.